O Centro e a Periferia na Poética e na Narrativa de Políbio Alves - Roque Nunes da Cunha (2023)
The literary production of the Paraiba writer Políbio Alves dos Santos presents itself as an innovative writing that takes a new look at the duality of the spatial relationship between writing from the center and writing from the periphery, fusing this vision into an aesthetic proposal that places the center of spatiality in the place where the voice of the narrator and the voice of the poetic self meet, and provokes the reader to delve into the reading and be modified by this vision of space, imprinting a new aesthetic vision on this space. Alves brings, in his poetics and prose, themes that range from the sublime to the everyday, working on the concept of space as a transforming factor in life and experiences from the mangrove mud, the dump rooms, the streets of Varadouro that transmute and they renew lives. This work aimed to analyze the space as a transforming element that appears in all his literary work as a proposal, or aesthetic plan of literary fruition, committed to innovations in the field of writing by short sentence, full of meanings, extraction of precise meanings in his dexterity vocabulary and focused on the “forgotten” layers of the population, which were erased from the official world view. Based on a theoretical framework of a sociological nature, this work was supported by Literature theorists such as Antonio Candido (2006), Jean-Cristophe Bailly (2021), Luís Alberto Brandão (2013) and Regina D'Alcastagnè (2015) to build the your theoretical debate and support your thesis. The discussions carried out in the body of the thesis allow us to conjecture that Políbio Alves transforms the concept of space not only as a static element in his artistic production, but also places it in the foreground of action as a dynamic agent of the characters, as well as a provocateur for the reader. It can be concluded that, from the readings and the debate made in the thesis, Políbio Alves proposes an aesthetic plan that unites space, time and memory as pillars of his aesthetic construction and the transformation of the spatial duality between the center and the periphery having the neighborhood of Varadouro as the epicenter of his poetics. To Alves, the center is where the poetic gaze and the narrative voice meet, fusing the urban space into a single manifestation of artistic and aesthetic worldview.